2020
DOI: 10.1007/978-3-030-47189-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling in the Tumor Microenvironment

Abstract: Dysregulated Wnt signaling plays a central role in initiation, progression and metastasis in many types of human cancers. Cancer development and resistance to conventional cancer therapies are highly associated to the tumor microenvironment (TME), which is composed of numerous stable non-cancer cells including immune cells, extracellular matrix (ECM), fibroblasts, endothelial cells (ECs), and stromal cells. Recently increasing evidence suggests that the relationship between Wnt signaling and the TME promotes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 136 publications
(144 reference statements)
1
13
0
Order By: Relevance
“…25 Targeting Rho-ROCK signaling by noncoding RNAs might be an effective way to modulate angiogenesis in the TME. 26,27 In this study, we revealed that circ_TNFRSF21 facilitated tube formation of HUVECs by sponging miR-3619-5p and upregulating ROCK2. Moreover, our results indicated that ROCK2 was directly prohibited by miR-3619-5p, which was consistent with a previous report.…”
Section: Discussionmentioning
confidence: 65%
“…25 Targeting Rho-ROCK signaling by noncoding RNAs might be an effective way to modulate angiogenesis in the TME. 26,27 In this study, we revealed that circ_TNFRSF21 facilitated tube formation of HUVECs by sponging miR-3619-5p and upregulating ROCK2. Moreover, our results indicated that ROCK2 was directly prohibited by miR-3619-5p, which was consistent with a previous report.…”
Section: Discussionmentioning
confidence: 65%
“…It is involved in leucocyte maintenance and renewal while promoting immune tolerance, immune evasion and limits the antitumor immune response. 52 Furthermore, Wnt/β-catenin signaling also plays a crucial role in EMT, thus, it enhances cancer stem cell maintenance. Based on these findings, we postulate that MIR155HG modulates tumor-immune interactions via the Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…CAMs mediate the adhesion of cancer cells not only to each other but also to stromal cells and ECM, namely, the tumor microenvironment (TME). The TME mainly comprises stable nonmalignant cells, including surrounding immune cells, extracellular matrix, fibroblasts, endothelial cells (ECs), blood vessels, and stromal cells ( 33 ).…”
Section: Cams In Cancers and Their Microenvironmentmentioning
confidence: 99%
“…SRGN is an ECM factor that binds to CD44 in an autocrine manner and acts by triggering MAPK and Wnt/β-catenin signaling in breast CSCs ( 80 ). Thus, CD44 is closely regulated by Wnt signaling ( 33 , 81 ).…”
Section: Cd44 and Endocrine-related Cancersmentioning
confidence: 99%